Orthodox Christianity, new age spirituality and vernacular religion: the evil eye in Greece - Roussou, Eugenia (Bloomsbury advances in religious studies, 2021)
1. Introduction -- 2. The New Age of Greek Religiosity: Orthodox Christianity and Beyond -- 3. Matiasma : the Energetic Interplay of Senses and Emotions -- 4. Ksematiasma : Healing, Power, Performance -- 5. Creative Syntheses through Material Culture: the Evil Eye in the Spiritual Marketplace -- 6. The Pluralistic Landscape of Greek Religiosity: Religion and Spirituality at a Global Age -- 7. Conclusion -- Bibliography -- Index